A Survey of Stakeholders to Determine Florida Sea Grant's 2006-2009 Programmatic Objectives for Coastal Communities and Water-Dependent Businesses - Robert Swett; Susan Fann (EDIS)
This publication was supported by the National Sea Grant College Program of the U.S. Department of Commerce’s National Oceanic and Atmospheric Administration (NOAA), Grant No. NA16RG-2195. It was compiled and edited by Robert Swett and Susan Fann. September 2005.